2021
DOI: 10.2147/ijgm.s340939
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Activating Transcription Factor 3 (ATF3) in Hepatoblastoma and Its Relationship with Ferroptosis

Abstract: Purpose The molecular mechanisms and signal pathways of ferroptosis in hepatoblastoma (HB) have not yet been clarified. In previous studies, activating transcription factor 3 (ATF3) was reported to be correlated with several tumors, but the clinical significance of ATF3 has never been determined. Herein, we investigated the clinicopathological value and mechanisms of ATF3 in regulating ferroptosis in HB. Methods The mRNA microarray and RNA-sequencing data of 402 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One study revealed that N6-methyladenosine modification enhances HB resistance to ferroptosis by inhibiting SLC7A11, thereby mediating therapeutic resistance ( 12 ). Another bioinformatic study reported that the ferroptosis driver ATF3 may serve as a biomarker for predicting HB occurrence ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study revealed that N6-methyladenosine modification enhances HB resistance to ferroptosis by inhibiting SLC7A11, thereby mediating therapeutic resistance ( 12 ). Another bioinformatic study reported that the ferroptosis driver ATF3 may serve as a biomarker for predicting HB occurrence ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Liu et al revealed that m6-methyladenosine modi cation in HB could enhance ferroptosis resistance of SLC7A11, providing a potential strategy for HB therapy14 . Li et al exhibited that down-regulated activating transcription factor 3 (ATF3) play a vital role in HB development by regulating ferroptosis15 . However, there are few research works on whether speci c ferroptosis-related genes regulate HB pathogenesis and prognosis at present.…”
mentioning
confidence: 99%